Digital Transformation In Education Management Optimizing Technology For Effective Learning - Thamrin, Putri Aulia; Nasuah, Risma; Talaohu, Nurfatima; Maharani; Almasi, Mustapha (The Faculty of Education and Teaching Training, 2024)
The integration of technology in education has now become a necessity. Digitalization in education opens up great opportunities in educational management to optimize effective learning. However, in Indonesia, educational digitalization poses a challenge in terms of equity. This article aims to examine how the digitalization of education management can improve the quality of learning and address the technology usage gap in Papua. This research uses a qualitative descriptive method with a literature review, analyzing various data from books and journals, and applying triangulation to obtain more comprehensive data. The results show that the integration of technology has a significant positive impact on the accessibility and efficiency of learning. However, Indonesia's geography hinders digitalization in all regions, especially in Papua. The remote areas of Papua with many 3T regions still use conventional models due to difficult access, limited internet, and a lack of competent human resources. There is a need for the improvement of human resource quality, the utilization of technology, and collaboration with the government and non-profit organizations.